ADMINISTRATION MECHANISM OF REAL ESTATE PROPERTY OF THE MINISTRY OF DEFENSE OF THE RUSSIAN FEDERATION - A. Yakovlev (Вестник университета)
The structure and functioning of the real estate administration system located in the Ministry of Defense of the Russian Federation have been considered. In Russia the possession, use and disposal of military property costs mansions in comparison with other federal property. The property administration of the Russian Ministry of Defense is inherent in a number of signs, including the autonomy of the military and the closeness of the administration process. Today only in the Central Federal District there are about 57 000 objects of military real estate.